Electoral systems and gender mainstreaming in transitional democracies: insights from Sudan’s path to inclusive governance - Juliet Eileen Joseph (Cogent Social Sciences)
This study examines how electoral systems affect democratic stability and gender mainstreaming in transitional nations, with a focus on Sudan. The research examines how electoral systems foster inclusive government, focussing on gender mainstreaming as a key to lasting peace. Anchored in theories of democratic transition, electoral authoritarianism and intersectional theory, the analysis considers how inclusive electoral practices can advance stability in fragile states. Anchored in theories of democratic transition, electoral authoritarianism, and intersectional theory, the analysis considers how Sudan’s electoral practices contribute to stability in fragile states. Empirical findings indicate that women’s participation in political processes significantly enhances peace outcomes and democratic legitimacy. Recommendations include electoral reforms that prioritize gender mainstreaming, support marginalized groups, and promote genuine democratic representation to foster long-term resilience in Sudan’s transitioning political landscape. These insights offer valuable guidance for policy frameworks and institutions working on post-conflict governance and gender equity.